2021
DOI: 10.1080/24733938.2021.2013522
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bio-banding on technical and tactical indicators of talent identification in academy soccer players

Abstract: The aim of this study was to examine the effect of bio-banding on technical and tactical markers of talent identification in 11-to 14-year-old academy soccer players. Using a repeated measures design, 92 players were bio-banded using percentage of estimated adult stature attainment (week 1), maturityoffset (week 2) and a mixed-maturity method (week 3). All players contested five maturity (mis)matched small-sided games with technical and tactical variables measured. Data were analysed using a series of Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Several proposals have been suggested to remove relative age bias including changing (Barnsley, 1988 ; Helsen et al, 2012 ) and rotating the cut-off dates (Barnsley, 1988 ), installing sport-specific cut-off dates (Musch and Grondin, 2001 ), and particular [i.e., age-ordered numbered soccer shirts and birthday banding (Kelly et al, 2020 )] talent identification strategies (Mann and van Ginneken, 2017 ). Maturity-related selection bias between players' differences has been addressed using maturity bio-banding (Reeves et al, 2018 ; Abbott et al, 2019 ; Macmaster, 2021 ; Towlson, 2021 ; Towlson et al, 2021a ), whereby players are grouped according to their maturation status (Cumming et al, 2017 ; Malina et al, 2019 ). Despite the relative success of some of the aforementioned methods to reduce RAE (i.e., birthday and bio-banding) and maturity selection bias (i.e., bio-banding), many proposed solutions can be difficult to implement and rely on the flexibility of coaches in how they structure games and training programs.…”
Section: Introductionmentioning
confidence: 99%
“…Several proposals have been suggested to remove relative age bias including changing (Barnsley, 1988 ; Helsen et al, 2012 ) and rotating the cut-off dates (Barnsley, 1988 ), installing sport-specific cut-off dates (Musch and Grondin, 2001 ), and particular [i.e., age-ordered numbered soccer shirts and birthday banding (Kelly et al, 2020 )] talent identification strategies (Mann and van Ginneken, 2017 ). Maturity-related selection bias between players' differences has been addressed using maturity bio-banding (Reeves et al, 2018 ; Abbott et al, 2019 ; Macmaster, 2021 ; Towlson, 2021 ; Towlson et al, 2021a ), whereby players are grouped according to their maturation status (Cumming et al, 2017 ; Malina et al, 2019 ). Despite the relative success of some of the aforementioned methods to reduce RAE (i.e., birthday and bio-banding) and maturity selection bias (i.e., bio-banding), many proposed solutions can be difficult to implement and rely on the flexibility of coaches in how they structure games and training programs.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst we acknowledge that PHV has been shown to occur at approximately 86% of estimated adult stature [12], bandings were defined as 'post-PHV' (�90% EASA) and 'pre-PHV' (<90%) to allow even distribution of players per category. Given that previous research has shown bio-banding to have little effect on players within the circa-PHV category [10,15,16], only players at either extreme of the maturation continuum were selected to participate in the study. Players anthropometric data was collated within the month prior to the testing period, extenuating the influence of biological growth on subsequent accurate maturity bandings.…”
Section: Participantsmentioning
confidence: 99%
“…In both conditions, players performed a standardised, 15-minute club led warm-up and contested 6 bio-banded and mixed maturity SSGs (total: n = 6) on an outdoor 4G surface, The SSGs were contested by teams of four players. This method has been previously used for the intention of talent identification within UK soccer academy practice [46] and previous bio-banding SSG research [10,15,16]. In addition, given the prevalence of the maturation selection bias with UK academy soccer programmes [3,43] the sample of players per academy deemed to be pre-PHV was finite.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations